2020
DOI: 10.2495/sdp200071
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Pyramid Trunk: The Three Axes of the Smart City Assessment Tool

Abstract: Smart Cities have changed from a purely technological paradigm to a holistic, integrated strategy, where the citizens play an important role in the decision-making process. Cities begin to understand the potential of integration approaches, interoperability of solutions, and start seeking strategic thinking when addressing new technologies. In this context, to implement a holistic strategy, city decision makers must have a tool that helps them to strategize according to their current state and then understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…SC provides an opportunity to achieve a desired, normative, dream city. Of late, SC has transformed from a purely technological paradigm to a holistic, integrated strategy (Correia et al, 2020) to achieve a desired city. As we saw, SCM allocates a central position to people and recognizes collaborative roles of smart technologies in enhancing economic potentialities of cities and achieving sustainable and resilient cities.…”
Section: Discussionmentioning
confidence: 99%
“…SC provides an opportunity to achieve a desired, normative, dream city. Of late, SC has transformed from a purely technological paradigm to a holistic, integrated strategy (Correia et al, 2020) to achieve a desired city. As we saw, SCM allocates a central position to people and recognizes collaborative roles of smart technologies in enhancing economic potentialities of cities and achieving sustainable and resilient cities.…”
Section: Discussionmentioning
confidence: 99%
“…Several smart city frameworks can be found in the literature [13][14][15][16][17][18]. However, there is a lack of a practical and accepted standard framework to guide and monitor the city's progress [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…in terms of city assessment, the existing frameworks have been mostly used to rank the cities, mixing up different concepts, and not consider the evolution noticed in the smart City concept. However, they present significant insights (see more at [68]). For example, sharifi [78] concluded that assessment tools do not consider indicators' interlinkages and correlations as well as local needs and participatory approaches; Ahyenniemi et al [59] demonstrated that smart City assessment tools are focused on social aspects and the sustainable Cities' on the environment; Huovila et al [79] concluded that 90% of the key performance indicators (KPis) from iso 37120 were focused on sustainability and the itu 4902 had a purely iCt-enabled indicator orientation.…”
Section: Stagementioning
confidence: 99%
“…Following Correia, teixeira and marques [68], the primary KPis will be collected from iso 37120, itu 4901 and mercer's annual quality of life survey. two axes shall be considered with two different approaches each:…”
Section: Stagementioning
confidence: 99%
See 1 more Smart Citation